The distribution of microplastics in water, sediment, and fish of the Dafeng River, a remote river in China - Shuo Liu (Elsevier, 2021)
Although rivers are one of the dominant pathways by which microplastics reach the oceans, reports on remote rivers are rare. Dafeng River is located in Guangxi Province, China, is an important water source and a habitat of a coastal dolphin, Sousa chinensis, which is a first-class national protected animal in China. In this study, we determined the distribution and characteristics of microplastics in the surface water, sediment, and fish of the river. During the dry and rainy seasons, the microplastics content of the surface water ranged from 3 × 10−4-2.5 × 10−3 items/L (7 × 10−4-0.12 items/m2) and 4 × 10−5-9 × 10−4 items/L (2 × 10−3-2.8 × 10−2 items/m2), while those in the sediment samples ranged from 9.4 to 50.3 items/kg (dry weight) and 0.0–21.3 items/kg, respectively. The pollution level during the dry season was approximately two to three times higher than that during the rainy season (P < 0.05). The estimated annual load of microplastics carried by the Dafeng River flow was 8.3 × 108 particles. The microplastics pollution in the Dafeng River was closely related with residential activities. The contents of microplastics in the digestive tracts and gills of fish ranged from 8 × 102 to 5.7 × 103 items/kg (0.3–6.7 items/individual) and 2 × 102 to 1.7 × 103 items/kg (0.1–3.0 items/individual), respectively. The proportion of blue particles in fish was significantly higher than that in the water and sediment, which may indicate that they prefer blue-colored items. The microplastics pollution levels in the water, sediment, and fish of the Dafeng River decreased in the following order: fish > sediment > surface water in terms of items/kg. The level of microplastics pollution in the Dafeng River was relatively low; however, that in aquatic organisms was more severe. Our work highlights the requirement for concern towards microplastics pollution in the organisms of remote rivers.